AN ANALYTICAL STUDY OF THE VIRTUES AND MERITS OF THE ASHARA MUBASHSHARA IN THE LIGHT OF THE QURAN AND SUNNAH - Tooba Irshad; Hadia Bibi; Shaista Shams; Kinza Hameed (Journal of Religion and Society, 2025)
This research paper presents an analysis of the virtues and merits of the Ashra Mubashra, the ten blessed companions of the Prophet Muhammad (peace be upon him) who were promised Paradise during their lifetime. These companions hold a significant place in Islamic history due to their unwavering faith, exemplary character, and immense sacrifices for the cause of Islam. The aim of this study is to highlight the importance, contributions, and esteemed status of these companions through a detailed examination of Hadith literature, including references from the Sihah Sitta (the six major Hadith collections) and various biographical sources. The paper reviews and analyzes the Hadiths that highlight the virtues of these ten companions and provides an evaluation of their authenticity based on established Islamic scholarship. Each companion's unique virtues are discussed individually, supported by historical events and the roles they played in the early expansion of Islam. Finally, the paper concludes with a summary of the spiritual and religious significance of the Ashra Mubashra, emphasizing their exemplary lives and the lessons they offer to the Muslim Ummah.This research aims to contribute to the field of Islamic studies by providing a thorough account of the merits of the Ashra Mubashra, serving as a valuable resource for scholars and offering inspiration and guidance for the broader Muslim community. Keywords: Ashra Mubashra, Virtues of Sahaba, Merits of Sahaba, Abu Bakr Siddiq, Umar Farooq, Uthman Ghani, Ali Al-Murtaza, Talha ibn Ubaidullah, Zubair ibn Al-Awwam, Abdur Rahman ibn Awf, Sa'd ibn Abi Waqqas, Saeed ibn Zayd, Abu Ubaidah ibn Al-Jarrah, Companions promised Jannah, Hadith and Athar, Virtues and Merits